150 best Eco house ideas - Serrats, Marta (New York : Collins Design and Loft Publications, 2010)
The stylish and sustainable homes in this book were built to reduce their impact on the environment and improve the quality of life of their occupants. These designs are proof that sustainability goes hand-in-hand with style and comfort.
Introduction -- Passive energy strategies --Active energy strategies -- Prefab constructions -- Innovative ideas.
Keywords: ARCHITECTURE ENVIRONMENTAL ASPECTS